2018
DOI: 10.1111/gcb.14430
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency greenhouse gas flux measurement system detects winter storm surge effects on salt marsh

Abstract: The physical controlling factors on coastal plant communities are among the most dynamic of known ecosystems, but climate change alters coastal surface and subsurface hydrologic regimes, which makes rapid measurement of greenhouse gas fluxes critical. Greenhouse gas exchange rates in these terrestrial-aquatic ecosystems are highly variable worldwide with climate, soil type, plant community, and weather. Therefore, increasing data collection and availability should be a priority. Here, we demonstrate and valida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Although several of the reviewed studies include measurements of CH 4 fluxes over several seasons and/or tidal cycles (Adams, Andrews, & Jickells, 2012; Bahlmann et al, 2015; Diefenderfer et al, 2018; Emery & Fulweiler, 2014; Li, Wang, et al, 2018), none of these studies continuously measure CH 4 flux over multiple annual cycles to capture changes driven by climate that may otherwise be missed. Continuous measurements of CH 4 flux over several years, daily and/or several times a season with greater spatial coverage, would help increase the accuracy of CH 4 flux estimates from VCEs as is shown in terrestrial systems (Ueyama et al, 2015).…”
Section: Studies Reviewedmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several of the reviewed studies include measurements of CH 4 fluxes over several seasons and/or tidal cycles (Adams, Andrews, & Jickells, 2012; Bahlmann et al, 2015; Diefenderfer et al, 2018; Emery & Fulweiler, 2014; Li, Wang, et al, 2018), none of these studies continuously measure CH 4 flux over multiple annual cycles to capture changes driven by climate that may otherwise be missed. Continuous measurements of CH 4 flux over several years, daily and/or several times a season with greater spatial coverage, would help increase the accuracy of CH 4 flux estimates from VCEs as is shown in terrestrial systems (Ueyama et al, 2015).…”
Section: Studies Reviewedmentioning
confidence: 99%
“…The one seagrass study that measured methane flux continuously for a few days reported maximum CH 4 emissions at night indicating that CH 4 oxidation was reduced (Bahlmann et al, 2015). In contrast, maximum mangrove and salt marsh CH 4 emissions can occur during the day (Yang et al, 2018), at night (Diefenderfer et al, 2018), or exhibit no diurnal cycle (Jha et al, 2014; Li, Dai, et al, 2018). Length of measurement period may play a role in these results as studies that measured CH 4 fluxes over an entire year did not find clear diurnal patterns (Jha et al, 2014; Li, Dai, et al, 2018), while studies performed over a few days noted diurnal differences in CH 4 flux (Bahlmann et al, 2015; Diefenderfer et al, 2018; Yang et al, 2018).…”
Section: Driversmentioning
confidence: 99%
See 1 more Smart Citation
“…Coastal ecosystems are sensitive to rapid and disproportionate hydrological and biogeochemical fluctuations with terrestrial, atmospheric, and oceanic origins including extreme precipitation events 57 , snow/ice melt 10 , accumulation and enhanced dry deposition of atmospheric pollutants 58 , extreme high tides, and storm surges 46,59 . Thus, hot momentsshort time periods with disproportionately high metabolic rates-may play a prominent, but typically ignored role in coastal ecosystem biogeochemical cycling.…”
Section: Challenges For Constraining Coastal Dynamicsmentioning
confidence: 99%
“…High temporal resolution measurements of different processes are thus needed to couple ecosystem responses (e.g., greenhouse emissions) with the underlying controls to properly represent hot moments in regional models and ESMs. While new technologies are emerging that allow highly resolved organic carbon or gas flux measurements 46,59 , there is a lack of consensus on how to appropriately scale lateral land-water carbon fluxes, or carbon emissions from either the bottom-up or top-down origin 8,65 .…”
Section: Challenges For Constraining Coastal Dynamicsmentioning
confidence: 99%